Management of Subintimal Position of Kissing Stents using Re-entry Catheter with Cone Beam-Computed Tomography Image Overlaid onto Live Fluoroscopy - Pescatori, Lorenzo C; Kobeiter, Hicham; Derbel, Haytham; Desgranges, Pascal; Tacher, Vania (Journal of Endovascular Resuscitation and Trauma Management, 2021)
Background: Several endovascular or surgical treatments have been proposed to treat total chronic occlusions of the iliac bifurcation. Nowadays, endovascular options are considered as a first choice because of the decreased perioperative morbidity–mortality. Nevertheless, unexpected intraoperative events may occur, such as dissection or rupture of the iliac artery. We report a case of inadvertent bilateral false-lumen kissing-stent positioning, rescued with stent extensions maneuvered using image fusion guidance. Case presentation: A 60-year-old male patient was referred to our department because of a severe bilateral claudication, 8 months after placement of an iliac kissing stent for common iliac artery occlusion. A computed tomography angiography (CTA) was performed, showing a bilateral dissection of the aorto-iliac bifurcation at the proximal part of the stents, which were placed into the false lumen; the distal part was placed into the true lumens (TL). Lower-limb perfusion was maintained by inferior mesenteric and hypogastric arteries. Because a CTA performed before the first endovascular intervention showed no dissection of the aortic bifurcation, the flaps were probably created during previous interventions. An endovascular revision was planned. After bilateral femoral access, the proximal part of the flap was pierced with a needle-based re-entry device, deployed under three-dimensional cone-beam CT image overlay with bi-planar fluoroscopy. The lumen patency was then restored with stent extensions up to the renal ostia. The final angiography showed stent patency. No complication occurred during the intervention. The patient was dismissed the following day, with good arterial femoral pulse and no further complications. An ultrasound color Doppler performed 1 month after the intervention showed satisfactory blood flow of both iliac and femoral arteries as well as a good flow in the lower limbs. Conclusions: The integration of modern 3D image guidance and novel endovascular devices allows for the management of adverse events using a minimally invasive approach.